Perlindungan Hukum Pemerintah Kabupaten Karawang Dalam Mengatasi Pelanggaran Atas Lingkungan Hidup Berdasarkan Peraturan Daerah Kabupaten Karawang Nomor 14 Tahun 2012 - Nur Izza, Yulia Erindra; Nurdin, Maharani (Fakultas Syariah INSURI Ponorogo, 2023)
Karawang Regency, which is currently the largest industrial city in Indonesia, has the possibility of a large risk of environmental pollution or damage. This can happen because of business activities that are not in accordance with the company's operational standards and also the Laws and Regulations. For this reason, this writing discusses the role of the Karawang Regency Government in overcoming and preventing violations of environmental protection due to company activities. And the form of social responsibility of PT Pindo Deli Pulp and Paper Mills II based on Regional Regulation of Karawang Regency No. 14 of 2012. This article uses a normative juridical research method with a statue approach and a case approach, in which the data collection technique uses a literature study derived from primary legal materials and secondary legal materials. The results of this study are that the Karawang Regency Government has the authority to supervise the implementation of environmental protection and management, which is based on Karawang Regency Regional Regulation Number 14 of 2012 concerning Environmental Protection and Management. In carrying out the supervision of environmental protection and management, the Government of Karawang Regency formed an Environmental Protection Agency (EPA) and also a Regional Environmental Monitoring Officer which was formed to facilitate the bureaucratic system in overseeing the implementation of environmental protection and management. And companies that violate the protection and management of the environment are absolutely responsible for the losses they cause.